Midlife Blood Pressure Variability and Risk of All-Cause Mortality and Cardiovascular Events During Extended Follow-up. (8th July 2021) - de Havenon, Adam; Delic, Alen; Yaghi, Shadi; Wong, Ka-Ho; Majersik, Jennifer J; Stulberg, Eric; Tirschwell, David; Anadani, Mohammad
Abstract: BACKGROUND: Studies demonstrate an association between visit-to-visit blood pressure variability (BPV) and cardiovascular events and death. We aimed to determine the long-term cardiovascular and mortality effects of BPV in midlife in participants with and without cardiovascular risk factors. METHODS: This is a post-hoc analysis of the Atherosclerosis Risk in the Community study. Long-term BPV was derived utilizing mean systolic blood pressure at Visits 1–4 (Visit 1: 1987–1989, Visit 2: 1990–1992, Visit 3: 1993–1995, Visit 4: 1996–1998). The primary outcome was mortality from Visit 4 to 2016 and secondary outcome was cardiovascular events (fatal coronary heart disease, myocardial infarction, cardiac procedure, or stroke). We fit Cox proportional hazards models and also performed the analysis in a subgroup of cardiovascular disease-free patients without prior stroke, myocardial infarction, congestive heart failure, hypertension, or diabetes. RESULTS: We included 9, 578 participants. The mean age at the beginning of follow-up was 62.9 ± 5.7 years, and mean follow-up was 14.2 ± 4.5 years. During follow-up, 3, 712 (38.8%) participants died and 1, 721 (n = 8, 771, 19.6%) had cardiovascular events. For every SD higher in systolic residual SD (range 0–60.5 mm Hg, SD = 5.6 mm Hg), the hazard ratio for death was 1.09 (95% confidence interval [CI] 1.05–1.12) and for cardiovascular events was 1.00 (95% CI 0.95–1.05). In cardiovascular disease-free participants (n = 4, 452), the corresponding hazard ratio for death was 1.12 (95% CI 1.03–1.21) and for cardiovascular events was 1.01 (95% CI 0.89–1.14). CONCLUSION: Long-term BPV during midlife is an independent predictor of later life mortality but not cardiovascular events. Graphical Abstract: